Pengembangan Trainer Automatic Transfer Switch sebagai Media Pembelajaran Praktik Instalasi Tenaga Listrik - Meliansyah, Pasa; Permata, Endi; Darmawan, Ilham Akbar (Jurnal Pendidikan Teknik Elektro, 2024)
Students in the field of electricity need to be prepared with competencies to become experts in ensuring the continuity of electricity supply to loads. The ATS system can support the automatic switching of power source connections from the main power source to the backup power source in the event of an outage. The increase in the use and utilization of solar panel technology should be balanced with the preparation of human resources as experts, especially in the field of electricity. The limitations of practical learning media in vocational education that support practical learning can hinder the achievement of student competencies. This study aims to determine the process of developing learning media for ATS trainers, to determine the feasibility and effectiveness of learning media in the learning process in the subject of Electrical Power Installation. The development research method is used in this study with the ADDIE development model. The feasibility value of learning media obtained from the assessment of media experts is categorized as very feasible. The feasibility value of the material obtained from the assessment of material experts is categorized as very feasible. The feasibility score based on the assessment of user responses obtained a score categorized as very feasible. The n-gain value obtained can be categorized into the category of medium effectiveness level.